Are the Politics of the Christian Right Linked to State Rates of the Nonreligious? The Importance of Salient Controversy. (December 2018) - Djupe, Paul A.; Neiheisel, Jacob R.; Conger, Kimberly H.
Hout and Fischer have made the repeated, controversial claim that the dramatic rise of "religious nones" in the United States is due to the prominence of the politics of the Christian Right. As the argument goes, the movement's extreme stands on gay rights and abortion make religion inhospitable to those who take more moderate and liberal positions. We take another look at this proposition with novel data drawing on expert reports and interest group counts that capture the prominence of the movement in each American state from 2000 to 2010. We attach these data to decennial religious census data on the unchurched, as well as estimates of the nones from Cooperative Congressional Election Study data. At stake is whether religion is independent of political influence and whether American religion is sowing its own fate by failing to limit taking extreme stands. Rising none rates are more common in Republican states in this period. Moreover, when the Christian Right comes into more public conflict, such as over same-sex marriage bans, the rate of religious nones climbs.